2002
DOI: 10.2151/jmsj.80.1103
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Responsible for the Maintenance of the 1998 South China Sea Summer Monsoon.

Abstract: This study examines the dynamic and thermodynamic characteristics associated with the evolution of the SCSSM of 1998 using the data from the South China Sea Monsoon Experiment (SCSMEX). The objective is to identify the physical processes that determined the active and inactive periods of the 1998 SCSSM.The intraseasonal variations in the activity of the 1998 SCSSM are found to be mainly controlled by the 30-60-day oscillation, but modified by the 10-20-day mode. Definition of the active and inactive period is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 24 publications
2
50
0
Order By: Relevance
“…Unit: ms À1 for wind and m 2 s À2 for kinetic energy (Mu and Li, 2000) 30-60-day mode occurred concurrently with bursting of the westerly monsoon at 850 hPa in this region (Mu and Li, 2000). Also based on the data from the SCSMEX in 1998, Chan et al (2002) have shown that the onset and maintenance of 1998 SCS summer monsoon were controlled by the 30-60-day oscillation and further modified by the 10-20-day mode. Chen and Chen (1995) previously indicated that the onset of the 1979 SCS summer monsoon occurs under the condition of a phase-lock between the 30-60-day and the 10-20-day modes over the Northern SCS.…”
Section: Intraseasonal Oscillations (Iso) and Teleconnection Patternsmentioning
confidence: 99%
“…Unit: ms À1 for wind and m 2 s À2 for kinetic energy (Mu and Li, 2000) 30-60-day mode occurred concurrently with bursting of the westerly monsoon at 850 hPa in this region (Mu and Li, 2000). Also based on the data from the SCSMEX in 1998, Chan et al (2002) have shown that the onset and maintenance of 1998 SCS summer monsoon were controlled by the 30-60-day oscillation and further modified by the 10-20-day mode. Chen and Chen (1995) previously indicated that the onset of the 1979 SCS summer monsoon occurs under the condition of a phase-lock between the 30-60-day and the 10-20-day modes over the Northern SCS.…”
Section: Intraseasonal Oscillations (Iso) and Teleconnection Patternsmentioning
confidence: 99%
“…Since the focus here is on the conditions prior to the SCSSM, this latter part will not be explored further. For more details of how the ISO modulates the monsoon active/break cycle, the reader is referred to the recent studies of Chan et al (2002) and Mao and Chan (2005). cyclonic anomalies in the circulation (Figure 3), which indicates contributions from the released latent heat of condensation.…”
Section: The 10-20-day Modementioning
confidence: 99%
“…Based on this selection criterion, 8 cycles are isolated for 3/6 mode, and 33 cycles for 1/2 mode, as well as 9 cycles of the 30-60-day oscillation and 32 cycles of the 10-20-day oscillation selected for dual mode during the period of 1979-2005. Then, each cycle is grouped into several different phases for composition, as in Chan et al (2002). That is, phase 3 is the peak of the active period, while phase 7 is the peak of inactive period.…”
Section: Compositing Techniquementioning
confidence: 99%
“…They further suggested that the SCS summer monsoon in 1979 was adjusted by the northward-propagation of the 30-60-day monsoon trough-ridge, and the SCS summer monsoon break occurred simultaneously with a phase lock in the northern SCS between the 30-60-day oscillation and the 10-20-day oscillation. According to the data from South China Sea Monsoon Experiment, Chan et al (2002) examined the evolution of the SCS summer monsoon in 1998 and found that the maintenance and break of the SCS summer monsoon in that year were controlled by the 30-60-day oscillation, and were further modified by the 10-20-day oscillation.…”
Section: Introductionmentioning
confidence: 99%